The Management of Security Interests for third Parties - the Security Agent in French Civil Law as a Model - - Taboukouyout, Youcef; Yazid, Dellal (Journal of Legal Studies and Researches, 2021)
The security interest’s evolution, with the appearance of guarantees based on property-security, that prompted the French legislator to adopt the security agent institution, an innovative mechanism for managing the third parties guarantees in syndicated loans. The security agent manages these guarantees on his own name and on behalf of creditors, in a patrimony allocated to this task. This research examine the provisions of this innovative mechanism, its effectiveness and its contributions to strengthening the credit.